Efektifitas Manajemen Sumber Daya Manusia Di BMT Sidogiri Capem Kencong - Farida Umi Choiriyah; Mahfiyah, Mahfiyah (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This study aims to determine the effectiveness of human resource management at BMT Sidogiri Capem Kencong which is seen from the aspect of human resource management of its employees, using a descriptive qualitative approach, namely research that focuses on data quality. This qualitative research examines the perspectives of participants with interactive and flexible strategies. This research is aimed at understanding social phenomena from the participant's point of view. data were collected through interview, observation and documentation techniques. Human Resource Management at BMT Sidogiri Capem Kencong The recruitment system at BMT Sidogiri Kencong Branch is very good by using two methods, namely internal and external recruitment. Besides that, there are special considerations in the recruitment system, where these considerations are prioritized for prospective employees from the Alumni of the Sidogiri Islamic Boarding School who are not required to be graduates of Islamic banking and Islamic economics. Because the most important thing in being an employee of BMT Sidogiri Kencong Branch is the inner bond so that it will bring up employees who have high loyalty to the organization. Meanwhile, in the process of fulfilling the demands of professionalism, BMT Sidogiri Kencong Branch uses a strategy by means of training and evaluation. Where the training is carried out at the end of the year which is carried out for 5 days and the evaluation is every month for the head of the BMT. Keywords :Management SDM,BMT Sidogiri